Helicobacter pylori infection prevalence declined among an urban health check-up population in Chengdu, China: a longitudinal analysis of multiple cross-sectional studies - Zou, Jin-Chen; Wen, Mao-Yao; Huang, Yan; Chen, Xin-Zu; Hu, Jian-Kun; , on behalf of the SIGES Research Group (Frontiers in Public Health, 2023)
Objectives: The efficacy of updated health policy in improving the generalization of Helicobacter pylori screening and eradication in the southwest China was assessed in a longitudinal analysis on multiple cross-sectional studies from an institution. Methods: In the 2009-2010, 2013-2014 and 2019-2021 periods, 8,365,16,914 and 18,281 urban observations from health check-up at West China Hospital were analyzed, respectively. The 14C-urea or 13C-urea breath test was used for Helicobacter pylori detection consistently. The protocol was reported elsewhere (PROSPERO Registration Number: CRD42019120764). Results: The overall prevalence of Helicobacter pylori was dramatically decreased from 53.1% to 30.7% over the past decade (OR=0.39, 95% CI 0.37-0.41), similarly in any sex-specific and age-specific subgroups. The age-specific prevalence kept ascending before 40 years old, and always peaked at 50-59 years. The longitudinal clearance was increased along with aging, and prevalence dropped of up to 22.6%, 25.1% and 23.6% in the 40-49, 50-59 and 60-69 years initial age groups, respectively. Conclusions: The generalization of massive Helicobacter pylori screening and eradication could greatly contribute to control Helicobacter pylori infection among urban health check-up population and be expected to lower gastric cancer incidence.